The use of augmented reality in cell structure learning to improve students’ conceptual understanding - Yulianto Kocu; Mivtha Citraningrum; Febrian Andi Hidayat (STKIP Persada Khatulistiwa Sintang, 2026)
This study is important due to the need for innovative learning media to help students understand abstract biological concepts effectively. This study aims to determine the effect of utilizing Augmented Reality (AR) in cell structure learning on the improvement of students' conceptual understanding at SMP Negeri 1 Aifat Timur. This study uses a quantitative approach with a quasi-experimental method and a nonequivalent control group design. The research sample consists of two classes, namely the experimental class using AR and the control class with conventional learning. The instrument used was a concept understanding test administered through a pretest and posttest. Data were analyzed using normality tests, homogeneity tests, independent sample t-tests, and N-Gain. The results showed a significant difference between the experimental and control classes with a significance value of 0.000 < 0.05. The average improvement (N-Gain) of the experimental class was 0.63 (moderate), higher than that of the control class at 0.38. These findings indicate that AR effectively enhances students' conceptual understanding. The novelty lies in applying AR as an interactive medium to visualize abstract cell structures at the junior high level, supporting improved biology education quality.